2022
DOI: 10.3390/biomedicines10102560
|View full text |Cite
|
Sign up to set email alerts
|

High Pretreatment Serum PD-L1 Levels Are Associated with Muscle Invasion and Shorter Survival in Upper Tract Urothelial Carcinoma

Abstract: Programmed death ligand-1 (PD-L1) is an immune checkpoint molecule and a widely used therapeutic target in urothelial cancer. Its circulating, soluble levels (sPD-L1) were recently suggested to be associated with the presence and prognosis of various malignancies but have not yet been investigated in upper tract urothelial carcinoma (UTUC). In this study, we assessed sPD-L1 levels in 97 prospectively collected serum samples from 61 UTUC patients who underwent radical nephroureterectomy (RNU), chemotherapy (CTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Similarly, patients with upper tract urothelial carcinoma with elevated sPD-L1 levels prior to therapy had a shorter duration of OS (median: ~ 10 months vs not reached at ~ 70 months, p = 0.006) following treatment with chemotherapy compared to patients with lower baseline levels (Fig. 4D) [89]. In small cell lung cancer patients receiving chemotherapy consisting of cisplatin-etoposide, elevated levels of sPD-L1 prior to therapy correlated with poor response to therapy and increased rates of death [48].…”
Section: Spd-l1mentioning
confidence: 83%
See 2 more Smart Citations
“…Similarly, patients with upper tract urothelial carcinoma with elevated sPD-L1 levels prior to therapy had a shorter duration of OS (median: ~ 10 months vs not reached at ~ 70 months, p = 0.006) following treatment with chemotherapy compared to patients with lower baseline levels (Fig. 4D) [89]. In small cell lung cancer patients receiving chemotherapy consisting of cisplatin-etoposide, elevated levels of sPD-L1 prior to therapy correlated with poor response to therapy and increased rates of death [48].…”
Section: Spd-l1mentioning
confidence: 83%
“…Plasma and serum levels of soluble immune checkpoints can change upon treatment with ICI, and in some cases, the magnitude of this change associates with clinical response. Three studies reported that sPD-L1 increased upon ICI therapy [81,84,89], while two observed sPD-L1 to remain constant upon ICI treatment (Table S1) [77,90]. In terms of clinical outcome, either a decrease or less of an increase in sPD-L1 upon treatment with ICI is correlated with improved clinical responses, with four studies (n = 204 patients) reporting similar findings (Table 2).…”
Section: Post-treatment Levels Of Spd-l1 After Ici As An Indicator Of...mentioning
confidence: 86%
See 1 more Smart Citation
“…This Special Issue aims to cover novel approaches in renal and urothelial cancers. We collected papers focused on novel approaches to urothelial cancers involving upper urinary tract and renal cancers that undertook original research focused on pre-clinical studies and biomarkers [ 9 , 10 , 11 , 12 ], prognostic models [ 13 , 14 , 15 ], the specific population of metastatic patients [ 16 ], and, finally, two narrative reviews [ 17 , 18 ].…”
mentioning
confidence: 99%
“…A recent paper by Szeles et al [ 10 ] focused on the relevance of the circulating soluble levels (sPD-L1) of programmed death ligand-1 (PD-L1) in upper tract urothelial carcinoma (UTUC). The authors prospectively collected serum samples from 61 UTUC patients treated with radical nephroureterectomy (RNU), chemotherapy (CTX), or immune checkpoint inhibitor (ICI) therapy.…”
mentioning
confidence: 99%